HUBUNGAN PENGETAHUAN, SIKAP MENGENAI SEKSUALITAS DAN PAPARAN MEDIA SOSIAL DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA DI BEBERAPA SMA KOTA SEMARANG TRIWULAN II TAHUN 2017 - Zidna Sabela Naja; Farid Agusyahbana; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Premarital sex behavior in adolescents is all the behavior of teenagers who are driven by the desire both with the opposite sex and same sex before the official relationship as husband and wife. The purpose of this study to determine the relationship and influence between knowledge, attitudes about sexuality, and exposure to social media with premarital sexual behavior in high school adolescents in the city of Semarang. The sample in this study was 271 with random sampling technique. Data collection was done with an online questionnaire. The results showed that the proportion of male sex respondents was 29.5% and female sex by 70.5% Based on the factors studied, respondents based on the age of most respondents aged 17 years ie 57.6%, 18 years old for 35,8% and besides the age of 19 and 20 years as much as 6.5%. Characteristics of respondents' social media behavior were 74.2% using social media for> 3 hours per day, 1-3 hours at 24.4% and <1 hour for 1.5% of respondents, and 98.8% using smartphone devices To open a social media account. Respondents had 4-6 social media accounts with the most applications, whatsapp and instagram 55.0%, other respondents had social media accounts > 7 of 23.2%, and <= 3 social media accounts of 21.8% . Statistic analysis was done by bivariate test with p value of chi square and it was concluded that there was significant relation between, attitude p = 0,0001, social media exposure p = 0,000 with premarital sexual behavior. And multivariate analysis with logistic regression and it can be concluded there is influence between attitude variable and social media exposure with premarital sexual behavior.